PENGARUH PENERAPAN MEDIA PEMBELAJARAN VIDEO TERHADAP HASIL BELAJAR SENI RUPA SISWA KELAS VII DI SMP NEGERI 1 TIMPEH - Deliza Oktavira, Drs. Suib Awrus, M.Pd., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2018)
This study aims to analyze the influence of the application of video media to the results of learning art class VII in SMP N 1 Timpeh. The hypothesis of the research is that there is a significant influence of the application of video learning media to the result of art learning of class VII in SMPN 1 Timpeh. Sampek in this research class VII students as many as 68 students consisting of experimental class and control class. The research data was collected through the learning result test and analyzed using t test. Research shows that the application of video learning media have a significant effect on the result of art study of class VII in SMPN 1 Timpeh.Keywords : learning outcomes, visual arts, video media